Effect of loading rates on behaviour of titanium alloys for aerospace structures - Tan, Kenneth Hong Yi. (2013)
Titanium and its alloys are highly desirable materials to be used in the aerospace industry due to its high strength and light weight. It is commonly used as airframe components on the airplane and could be subjected to different impact velocity. In this project, development of the microstructure of two types of titanium –CP-Ti and Ti-6Al-4V compressed at quasi-static and dynamic rates were investigated.